Understanding Sarinah as an Arena for Feminism Education Based on Local Culture: Memahami Sarinah Arena Pendidikan Feminisme Berbasis Budaya Lokal - Nyoman Suwarta; Dwi Astutiek; Edi Dwi Riyanto; Ahmad Nurefendi Pradana; Bambang Kusbandrijo; Yopi Lutfi Subargo (Academia Open, 2024)
General Background: Feminism education is crucial for fostering mutual respect and understanding of gender differences, emphasizing the social identity of archipelago feminism. This approach embraces the values of womanhood rooted in Indonesian culture and customs. Specific Background: The book "Sarinah" by President Sukarno offers a foundational perspective for exploring the historical and cultural significance of feminism education in Indonesia. Knowledge Gap: Despite analyses of "Sarinah" focusing on feminist values and Marxist literary criticism, research on the specific educational arena of feminism in Indonesia is limited. Aims: This study aims to analyze the Indonesian feminism education arena as presented in "Sarinah," using a qualitative methodology, including literature review and event interpretation. Results: The analysis identifies four key aspects: the third phase of civilization evolution, the role of intelligence, motivations of Indonesian feminism, and external influences such as society, family, and education systems. Novelty: The study highlights the distinctiveness of feminism education in Indonesia by focusing on local cultural values. Implications: The research emphasizes integrating cultural and traditional values in feminism education to promote gender equality. It calls for empowering women, recognizing their equal capabilities to men, and eliminating discrimination based on gender, class, or ethnicity. Highlights: Cultural Relevance: Emphasizes aligning feminism education with Indonesian cultural values. Key Factors: Identifies intelligence, motivation, and societal influences in the education arena. Empowerment: Highlights the need to empower women and address barriers to gender equality. Keywords: Pendidikan Feminisme, Arena, Adat, Budaya Nusantara